1992
DOI: 10.1161/01.cir.86.2.420
|View full text |Cite
|
Sign up to set email alerts
|

Elevated concentrations of endogenous ouabain in patients with congestive heart failure.

Abstract: BACKGROUND An endogenous digitalis-like compound in mammals has long been postulated, but only recently has a substance indistinguishable from ouabain been identified in human plasma. Because of the potential significance of such a substance in patients with congestive heart failure, we sought to evaluate the pathophysiology of endogenous ouabain in these individuals. METHODS AND RESULTS Using an immunoassay, we determined plasma ouabain concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
127
0
6

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(139 citation statements)
references
References 25 publications
6
127
0
6
Order By: Relevance
“…Although several studies have shown a correlation between elevated endogenous cardiac glycosides and certain pathological conditions, the physiological function of endogenous cardiac glycoside-like compounds is still uncertain (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have shown a correlation between elevated endogenous cardiac glycosides and certain pathological conditions, the physiological function of endogenous cardiac glycoside-like compounds is still uncertain (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17). In addition, marked increases in endogenous ouabain-like compounds occur in congestive heart failure, both in animal models and human patients (18)(19)(20). One concern raised with respect to endogenous cardiac glycoside-like compounds is that they occur in levels which may not significantly inhibit the Na,K-ATPase.…”
mentioning
confidence: 99%
“…Second, the activity of ouabain on Na/K ATPase might be dose-dependent. Since endogenous ouabain-like substance is also present in human body at pico-tonanomolar ranges, suggesting that the level of endogenous ouabain in leukemic patients might be too low to affect NF-κB and that frequent infusion of exogenous ouabain to maintain plasma concentration high enough might be needed to sustain the inhibition of NF-κB [14,15] . If so, systemic toxicity might be the limiting factor for its use especially in the elderly patients which constitute the bulk of leukemic patients.…”
Section: Research Highlightmentioning
confidence: 99%
“…The identification of cardiac glycoside-like molecules in mammals has led to the proposal that these compounds are natural regulators of Na,K-ATPase in vivo (7)(8)(9)(10). Several studies have shown a correlation between these cardiac glycoside-like molecules and certain pathological conditions, such as hypertension and heart failure (11)(12)(13)(14)(15)(16)(17). Plasma levels of these putative ligands for the Na,KATPase are high in several animal hypertension models, as well as in human essential hypertension and preeclampsia (11-14, 18, 19).…”
mentioning
confidence: 99%
“…Plasma levels of these putative ligands for the Na,KATPase are high in several animal hypertension models, as well as in human essential hypertension and preeclampsia (11-14, 18, 19). In addition, marked increases in peripheral and central endogenous ouabain-like compounds occur in animal models of congestive heart failure as well as in human patients (15)(16)(17). However, it is still difficult to draw definitive conclusions regarding the specific function of these molecules in pathophysiology.…”
mentioning
confidence: 99%